Dessimination of information in the framework of the British Council "English for Universities" project - Garmash, Sergii; Sadkovska, V. A. (Національний університет "Одеська юридична академія", 2017)
The given article is the authors` continuation of research papers dealing with sharing experience in traning during the process of learning English for specific purposes in the framework of the project "English for Universities". The objectives of this article are presentation new approaches in ESP-traning, solving the problems arisen during this process, description essentials and outcomes of this process. A detailed analisys of course objectives is given in the article. It is specially noted that we all live in the epoch of globalization with its positive and negative features and we all change with our changing world.
Поширення інформації у рамках проекту Британської Ради "Англійська мова для університетів"
Keywords: ESP; course objectives; essentials; outcomes; traning process; transformational change; globalization; глобалізація; процес навчальний; зміни трансформаційні